Pengaruh Indeks Pembangunan Manusia (IPM), Upah Minimum Dan Tingkat Pengangguran Terbuka Terhadap Jumlah Penduduk Miskin Di Provinsi Kalimantan Selatan Tahun 2010-2020 - Ammaliah, Nurul; Suherty, Lina (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study aims to analyze whether the variables of Human Development Index (HDI), Minimum Wage and Open Unemployment Rate have a significant effect simultaneously and partially on the number of poor people and to analyze the most dominant variable affecting the number of poor people. The scope of this research takes the area of South Kalimantan Province. The type of data used is secondary data obtained from documentation and literature at agencies related to this research which will be processed by multiple linear regression analysis and simultaneous tests and partial tests. The results of this study are the Human Development Index (HDI), Minimum Wage and Open Unemployment Rate simultaneously and partially have a significant effect on the number of poor people. The Open Unemployment Rate is the most dominant factor affecting the number of poor people.